An Improved Training Method For Wavelet Neural Networks For Solving Ordinary And Partial Differential Equations - Tan, Lee Sen (2022)
Differential equations (DEs) have been widely used for modelling countless studies and applications in various disciplines. In recent years, artificial neural networks (ANNs) have gained attention in solving DEs in a more efficient way to approximate solutions of DEs. In this thesis, wavelet neural networks (WNNs) were employed and programmed to solve ordinary differential equations (ODEs) and partial differential equations (PDEs).